(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article is devoted to defining the role of Culture in a highly complex pro-cess of development and manifestation of the mentality of ethnic groups and nations. The author states that the culture of human communities were formed naturally but were influenced by certain genetic and geo-political conditions of their life. These regulate, first of all, the processes of collective mental activity, bringing forth and defining the nature of the mentality of these people.